Analisis Kemampuan Penalaran Matematis Siswa SMP Pada Materi Himpunan - Nabilah Widyasari Lesmana (Program Studi Pendidikan Matematika, Universitas Majalengka, 2022)
This study aims to determine the mathematical reasoning ability of 8th grade junior high school students. The subjects of this study were 8th grade students in one of the junior high schools in Tirtamulya sub-district, Karawang regency. The methods and approaches used in this research are descriptive research methods with a qualitative approach. The instrument in this research is a mathematical reasoning ability test instrument with a set of 5 questions. Data analysis techniques used in this study are data reduction, data presentation, and inference. The results of this study in the high category there are 5 students with a percentage of 17,86%, in the medium category there are 18 students with a percentage of 64,29%, and in the low category there are 5 students with a percentage of 17,86%. It can be concluded that the mathematical reasoning ability of the 8th graders at the school with the set material is in the medium category.